Activated carbon-derived from durian peels for the adsorption of methylene blue dye - Ninh, Duc Bao; Vu, Minh Duc; Hoang, Viet Anh; Vu, Duc Loi; Kim, Chang Soo; Nurwahid, Imam Hidayat (Taylor & Francis, 2025)
This study introduces a novel application of durian peel-a widely discarded agricultural waste-as a high-performance, cost-effective adsorbent, offering a sustainable alternative to commercial activated carbon in dye-contaminated wastewater treatment. Systematic comparison on the characteristics and methylene blue adsorption performance of synthesized material and a commercial activated carbon (AC) was performed. The micropores and mesopores were observed on DP and AC, in which the total area in pore of DP (33.83 m2/g) is much larger than AC (0.072 m2/g) while the overall surface area was similar (about 583 m2/g) due to deference of pore width. The DP exhibited a maximum adsorption capacity of 96.7 mg/g for a wide range of pH, which is much higher than AC (43.3 mg/g) and other biomass-based adsorbents reported in the literature. The adsorption kinetics of methylene blue were best described by the pseudo-second-order model (R2 approximate to 0.999), indicating that chemisorption is the dominant mechanism. Additionally, the intraparticle diffusion model showed a multi-linear trend, suggesting that both surface adsorption and subsequent diffusion into the mesopores and micropores contribute to the overall process. Finally, chromatographic operation of MB using fix-bed column was investigated and analyzed using the Thomas and Yoon-Nelson dynamic models. The results indicate that the fixed-bed column with DP has high potential for application in wastewater treatment, although further studies on the material's regeneration need to be conducted in the future.